Rapid evolution of decreased host susceptibility drives a stable relationship between ultrasmall parasite TM7x and its bacterial host - Bor, Batbileg; McLean, Jeffrey S.; Foster, Kevin R.; Cen, Lujia; To, Thao T.; Serrato-Guillen, Alejandro; Dewhirst, Floyd E.; Shi, Wenyuan; He, Xuesong (Proceedings of the National Academy of Sciences - PNAS, 2018)
Around one-quarter of bacterial diversity comprises a single radiation with reduced genomes, known collectively as the Candidate Phyla Radiation. Recently, we coisolated TM7x, an ultrasmall strain of the Candidate Phyla Radiation phylum Saccharibacteria, with its bacterial host Actinomyces odontolyticus strain XH001 from human oral cavity and stably maintained as a coculture. Our current work demonstrates that within the coculture, TM7x cells establish a longterm parasitic association with host cells by infecting only a subset of the population, which stay viable yet exhibit severely inhibited cell division. In contrast, exposure of a naïve A. odontolyticus isolate, XH001n, to TM7x cells leads to high numbers of TM7x cells binding to each host cell, massive host cell death, and a host population crash. However, further passaging reveals that XH001n becomes less susceptible to TM7x over time and enters a long-term stable relationship similar to that of XH001. We show that this reduced susceptibility is driven by rapid host evolution that, in contrast to many forms of phage resistance, offers only partial protection. The result is a stalemate where infected hosts cannot shed their parasites; nevertheless, parasite load is sufficiently low that the host population persists. Finally, we show that TM7x can infect and form stable longterm relationships with other species in a single clade of Actinomyces, displaying a narrow host range. This system serves as a model to understand how parasitic bacteria with reduced genomes such as those of the Candidate Phyla Radiation have persisted with their hosts and ultimately expanded in their diversity.